Facial recognition I - Ting, Shou Xuan. (2013)
In this project, Principal Component Analysis (PCA), one of the methods in Facial Recognition will be discussed. The objectives of the project is to research on PCA, involving the understanding of the concept, implementing it with C++ language, conducting experiments and identifying its strengths and weaknesses.